Life goals of juvenile detainees - Vispo, Vidary Ann A.; Gabriel, Florenda S. (2006.)
The experience of incarceration among juvenile in conflict with the law has an impact on their aspirations of a better future. This exploratory study aimed to describe the life goals of juvenile detainees in terms of their long-term goals, their short-term and intermediate goals, and the perceived factors influencing their long-term goal attainment. Ten male juvenile detainees from Marikina Jails were purposely chosen with the assistance of the Bureau of Jail Management and Penology (BJMP). Data was gathered through a drawing activity and semi-structured interviews. Content analysis of the responses revealed that juvenile detainees set specific and relevant long-term goals focused on either acquiring valuable possessions or having a viable occupation. The respondents set goals linked to their past experiences and to a desired quality of life for themselves and their families. Their short-term and intermediate goals involved continuing their studies or working for a living. They believed that what can help them attain their long-term goals are their own selves, families and friends while the factors that they perceived can hinder them are their vices and peers. Juvenile detainees exhibited some aspects of resiliency reflected in their sense of hope for the future, their desire to be self-reliant and self-governing and their positive outlook in coping with life's adversities.
Thesis (BS Home Economics)--University of the Philippines Diliman.
Keywords: Juvenile delinquents -- Philippines